Juliao Sarmento: Noites Brancas- Retrospectiva - Fernandes, Joao; Lingwood, James; Sarmento, Juliao (Hatje Cantz; Fundacao Serralves, 2012)
Exhibition catalog. Nov 2012-Mar 2013. An exhibition series of artworks and video installations.
Portuguese
Keywords: N4390-5098 Visual Arts- Exhibitions